The Effectiveness of Antenatal Counseling on the Level of Knowledge in Overcoming First Trimester Pregnancy Problems at Manembo-nembo Hospital - Lois C Henderang; Rani Safitri (The Journal General Health and Pharmaceutical Sciences Research, 2025)
The first trimester of pregnancy is a crucial phase characterized by various physiological and psychological changes that can cause complaints in pregnant women. Adequate knowledge about these changes is essential for mothers to recognize pregnancy problems and take appropriate action. This study aims to assess the effectiveness of antenatal counseling on pregnant women's knowledge in dealing with first trimester pregnancy problems at Manembo-nembo Hospital, Bitung City. The study used a quasi-experimental design with a one-group pretest-posttest approach on 28 respondents selected through total sampling. The intervention was structured antenatal counseling that covered physiological changes, common complaints, danger signs, and their management. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results showed an increase in the average knowledge score from 42.18 to 61.75, with a p-value = 0.000. The high knowledge category increased from 14.3 % to 64.3%, while the low knowledge category decreased from 50% to 7.1%. These findings indicate that antenatal counseling is effective in increasing pregnant women's knowledge about first-trimester pregnancy issues, thereby supporting the readiness and health of both mother and fetus from the beginning of pregnancy.